2004
DOI: 10.7326/0003-4819-141-9-200411020-00007
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Computed Tomographic Angiography and Magnetic Resonance Angiography for Diagnosing Renal Artery Stenosis

Abstract: Computed tomographic angiography and MRA are not reproducible or sensitive enough to rule out renal artery stenosis in hypertensive patients. Therefore, DSA remains the diagnostic method of choice. *For a list of the other investigators and research coordinators who participated in RADISH, see the Appendix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
113
1
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 326 publications
(122 citation statements)
references
References 32 publications
1
113
1
7
Order By: Relevance
“…We performed systematic RA in consecutive AMI patients, regardless of other risk factors suggesting RAS (severe hypertension, PAD, or abdominal bruits). Data showed concordant values of RAS prevalence in AMI (16.6%) to those reported in well‐recognized risk groups (suspected renovascular hypertension5, 30—14.1%, hypertension and diabetes mellitus31—17.1%, chronic CAD5, 32, 33—9.1% to 10.8%) but lower values than in patients with chronic heart failure34—54.1%, aortic abdominal aneurysm35—38%, end‐stage renal disease36—40.8%. Differences between reports are driven by inclusion of patients with different stages of atheromatous disease and inflammation.…”
Section: Discussionsupporting
confidence: 65%
“…We performed systematic RA in consecutive AMI patients, regardless of other risk factors suggesting RAS (severe hypertension, PAD, or abdominal bruits). Data showed concordant values of RAS prevalence in AMI (16.6%) to those reported in well‐recognized risk groups (suspected renovascular hypertension5, 30—14.1%, hypertension and diabetes mellitus31—17.1%, chronic CAD5, 32, 33—9.1% to 10.8%) but lower values than in patients with chronic heart failure34—54.1%, aortic abdominal aneurysm35—38%, end‐stage renal disease36—40.8%. Differences between reports are driven by inclusion of patients with different stages of atheromatous disease and inflammation.…”
Section: Discussionsupporting
confidence: 65%
“…Later work using CE-MRA, such as the RADISH and DRAS-TIC trials (4,5) predominantly focused on investigating hypertensive patients with a lower disease prevalence, and yielded lower specificities and particularly lower sensitivities. This can at least in part be ascribed to a lack of spatial resolution in the CE-MRA techniques used at the time of those trials, which was only adequate to characterize ostial main renal artery disease.…”
Section: Atheroscelroticmentioning
confidence: 99%
“…While it provides a more accurate diagnosis than ultrasound, CE-MRA carries significantly less risk than the "gold standard" conventional angiography (CA) (6 -11). However, a recent study based on the routine use of CE-MRA showed that it was relatively less effective for grading RAS and insensitive for detecting distal RA disease, such as fibromuscular dysplasia (12). While there is clearly a role for renal CE-MRA as a noninvasive tool in diagnosing RA disease, there is a need for improvement in its ability to precisely depict RAs.…”
Section: Contrast-enhanced Mr Angiography (Ce-mra)mentioning
confidence: 99%